Red Pigment Production By Monascus Purpureus In Stirred-Drum Bioreactor - Mohamad Al Amin, Razali; Farhan, Mohd Said (Razi Publishing, 2017)
Several studies has been conducted to economically cultivate the Monascus sp. However, the potential of using stirred drum bioreactor in solid state fermentation (SSF) for Monascus sp. cultivation has been relatively understudied. Oil palm frond (OPF) petiole has been used as a potential substrate due to its nutritional contents and to add more value to local agricultural waste. This study reports the production of red pigment by Monascus purpureus FTC 5357 in a 2.3 L bench top - stirred-drum bioreactor. The fungus was grown on moistened OPF substrate (60 % (w/w)) supplemented with 2% (w/w) of soy meal peptone. The effects of different aeration rates (0.3-1.0 vvm of humidified air), agitation programme (4-8 cycles per day), and substrate load capacity (25-40 % (v/v) of total drum capacity) on red pigment production are reported. Aeration rate showed a positively correlated interaction to red pigment production in which the highest red pigment were produced using1.0 vvm (6.09 AU/g dry solid), and non-aerated culture showed the lowest red pigment production (0.81 AU/g dry solid). The agitation programme was also showing the positive trend of interaction, in which 8 cycles per day showed the highest red pigment production (4.34 AU/g dry solid) and 4 cycles per day agitation showed the lowest red pigment production.The red pigment production was peaked at 30% (v/v) drum loading capacity (5.61 AU/g dry solid) and the lowest at 25% (v/v) (0.89 AU/g dry solid), whereas 40% (v/v) substrate capacity was incapable of being mixed due to low power output of agitating motor. Results suggested that OPF was a potent source of substrate for the cultivating Monascus purpureus using SSF and all 3 factors (aeration, substrate load capacity and agitation programme) were significantly influenced the red pigment production.